Karakteristik dan Distribusi Spasial Habitat Positif Larva Nyamuk Anopheles spp. Berdasarkan Curah Hujan - Noper Tulak; Handoko Handoko; Rini Hidayati; Upik Kesumawati Hadi; Lukman Hakim (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Malaria is still a public health problem in Jayapura City. The disease is spread throughout the region withvarying number of cases. Increased transmission of malaria is affected by local conditions, including rainfall,habitat characteristics and larval habitats distribution. The aims of study were to describe habitat characteristicsand spatial distribution a habitat of positive of an Anopheles larvae spp based on rainfall in Heram District,Jayapura City. The method used is field observation with descriptive and statistical analysis approach. The resultsshowed that there were 6 breeding site Anopheles Mosquito in Heram District, namely rain puddle, puddles,moats, ponds, rivers and former tire tread. The habitat was found in Waena and Yabansai village. The larvalhabitat area is 0.04-28 m2, water depth 5-115 cm, water temperature 26.7-3.7 and water pH 6.7-7.7. A habitat ofpositive of an Anopheles larval spp were significantly affected by rainfall ie puddle (p=0.000; r=0.69), rain puddle(p=0.000; r=0.87), moats (p=0.000; r=0.57), former tire tread (p=0.047; r=0.34), pond (p= 0.000; r=0.57) andrivers (p=0.007; r=0.46 ) with determinant coefficients ranging between 0.11-0.77. Conclusion of the results ofthe study showed that rainfall affected a habitat of positive of an Anopheles larval spp in Heram District